Identifying critical behavioral gaps in standard precautions among healthcare workers: a CSPS-based study at an academic hospital in Yogyakarta - Marselinus Edwin Widyanto Daniwijaya; Anwar Rovik; Nesti Desi Ari; Purwadi Sujalmo; Ratna Dewi Puspita (Berita Kedokteran Masyarakat, 2026)
Purpose: Compliance with standard precautions is essential to mitigate healthcare-associated infections (HAIs) and occupational hazards. However, behavioral gaps often persist despite institutional policies. This study aimed to evaluate compliance with standard precautions among healthcare workers at Universitas Gadjah Mada (UGM) Academic Hospital. Methods: This cross-sectional study was conducted in 2024 among 120 healthcare workers across the outpatient, inpatient, and emergency units at UGM Academic Hospital in Yogyakarta. Participants were selected according to predefined inclusion and exclusion criteria. Adherence was assessed using the 20-item Compliance with Standard Precautions Scale (CSPS), with responses recorded on a 4-point Likert scale (ranging from never to always). Data were analyzed using descriptive statistics and the Kruskal-Wallis test to assess the significance of demographic factors. Results: The mean compliance score was 80.458, and 66.67% of participants were categorized as having "Moderate" compliance. Critical deficits were identified in needle recapping (Item 4; score 67/120) and ocular protection (Item 13; score 67/120). Work duration had no significant effect (p > 0.05), whereas educational background significantly influenced compliance (p < 0.05), with Diploma IV and Bachelor-graduated staff outperforming those with advanced specialist or doctoral degrees. Compliance levels were consistent across all workplace units, with no statistically significant differences (p > 0.05). Conclusion: Selective compliance remains a challenge in clinical settings. Institutional interventions should move beyond theoretical training to prioritize targeted behavioral reinforcement for staff at all educational levels.